ICHTHYOFAUNAL DIVERSITY OF SASTHAMKOTTA RAMSAR LAKE, KERALA, INDIA - GIRIJAKUMARI, S.; NELSON, P. A.; SMRITHY, R.; KUMAR, A. BIJU (Journal of the Inland Fisheries Society of India, 2022)
The information about the abundance and distribution of fishes of the aquatic biotope forms the basic step in assessing the fishery resources and their management. Monitoring the occurrence of species and their population has been the basis for assessing the effects of environment impacts (Spellerberg, 1993). Fish fauna of an aquatic habitat may undergo changes in diversity and composition or local extinctions due to anthropogenic interventions and climatic variations. In order to frame effective conservation measures for lakes, better insight into the diversity, abundance and distribution of dominant components of biodiversity such as fish in the lacusrtine ecosystem is required.